CuAlMnV shape memory alloy thin film based photosensitive diode. (1st March 2020) - Canbay, C. Aksu; Tataroğlu, A.; Farooq, W.A.; Dere, A.; Karabulut, Abdulkerim; Atif, M.; Hanif, Atif
Abstract: In the present work, the polycrystalline quaternary shape memory alloy (SMA) using composition of Cu-10.24 Al-3.13 Mn-0.41 V (wt%) was prepared with arc melting technique. The produced SMA was characterized by X-ray diffraction (XRD) and differential scanning calorimetry (DSC). In order to fabricate the Schottky diode, the SMA was utilized as a Schottky contact on n-Si. The admittance (Y = G + iωC) measurements were performed at different frequencies while the current-voltage (I–V) measurements of the prepared diode were performed at different light intensity conditions. The reverse bias current measured under illumination was found to be greater than the condition of dark. The obtained results approve that the diode displays a photoconducting behavior. The electrical parameters of diode were calculated from I–V data. Besides, the frequency impacts on the capacitance and conductance characteristics with regards to voltage were investigated. The experiments suggest that the fabricated diode could be chosen in the applications of the optoelectronic devices.